2008
DOI: 10.1111/j.1475-2743.2008.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate and mode of application of the urease inhibitor N‐(n‐butyl) thiophosphoric triamide on ammonia volatilization from surface‐applied urea

Abstract: A laboratory study evaluated the effect of rate (0, 100, 250, 500, 750 or 1000 mg ⁄ kg) and mode of application of the urease inhibitor N-(n-butyl) thiophosphoric triamide (nBTPT) (coating the urea granule, adding to the urea melt or adding to urea ammonium nitrate (UAN) solutions) on NH 3 volatilization from urea, at three temperatures (5, 15 and 25°C), with four contrasting soil types. Daily ammonia loss was measured for up to 21 days after surface N application, using ventilated soil enclosures. Ammonia lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 9 publications
2
82
0
6
Order By: Relevance
“…N, in coffee orchard, relating to climate data (c). The pH in the soil surface layer (0-5 cm) is one of the chemical attributes that mostly affects the volatilization of ammonia to the atmosphere, and an increase in its value accelerates the loss (Watson et al, 2008;Menendez et al, 2009). In this study, the soil pH in the 0-5 cm layer was reduced from the 1 st to the 3 rd N fertilization of coffee (Table 3).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…N, in coffee orchard, relating to climate data (c). The pH in the soil surface layer (0-5 cm) is one of the chemical attributes that mostly affects the volatilization of ammonia to the atmosphere, and an increase in its value accelerates the loss (Watson et al, 2008;Menendez et al, 2009). In this study, the soil pH in the 0-5 cm layer was reduced from the 1 st to the 3 rd N fertilization of coffee (Table 3).…”
Section: Resultsmentioning
confidence: 69%
“…Several compounds have been found to reduce the conversion of urea [(NH 2 ) 2 CO] into ammonium and, ultimately, ammonia in soil (Roberts, 2014). The main substances and elements that have been used for this purpose are NBPT (Watson et al, 2008;Cantarella et al, 2008;Menendez et al, 2009;Pereira et al, 2009;Trenkel, 2010;Silva et al, 2011), copper (Cu) and boron (B) (Krajewska;Zaborska;Chudy, 2004;Heringer, 2008;Gabrovska;Godjevargova, 2009;Faria et al, 2013;Nascimento et al, 2013;Stafanato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NBPT delays the rate of urea hydrolysis to NH 4 + -N and hence moderates the localised zones of high pH and NH 4 + -N concentrations, which result from urea hydrolysis and which are conducive to NH 3 volatilisation. The urease inhibitor has been shown to be highly effective at low concentrations (<500 ppm by weight of urea), lowering NH 3 losses from surface-applied urea (Watson et al, 2008) and increasing yield and N uptake compared with unamended urea (Watson et al, 2009). In the UK, field trials on grassland and tillage land showed that NBPT reduced ammonia emissions from untreated granular urea by 73% on average when used at a concentration of 500 or 1000 mg kg -1 (Chambers and Dampney, 2009).…”
Section: Urease Inhibitors (Uis)mentioning
confidence: 99%
“…Consequently, the ammonium (NH 4 + -N) and nitric (NO 3 --N) forms are also diminished. These forms of urea are the most labile for ammonia volatilization, de-nitrification and leaching in the soil-plant-atmosphere (Grohs et al, 2011;Pereira et al, 2009;Sanz-Cobena et al, 2008;Scivittaro et al, 2010;Stafanato et al, 2013;Watson et al, 2008).…”
Section: Nitrogen Loss By Ammonia Volatilizationmentioning
confidence: 99%
“…Moreover, the industry should aim to minimize negative environmental impacts, avoid mineral leaching into the water table or volatilization, and minimize the emissions of N oxides (a greenhouse gas) (Novoa;Tejeda, 2006;Stehfest;Bouwman, 2006;Vilain et al, 2014). These objectives have been achieved by aggregating available technologies with conventional fertilizers, such as urea, by reducing N losses and by increasing agronomic efficiency (Watson et al, 2008;Trenkel, 2010).…”
Section: Introductionmentioning
confidence: 99%